2004
DOI: 10.1016/s1471-0153(03)00064-3
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between religious orientation and eating disturbances

Abstract: The relationship between religion and eating concerns is receiving increasing empirical attention. The current investigation sought to examine the relationship between eating attitudes and religious orientation, utilizing the fourfold typology of religious orientation. A curvilinear relationship was found between religious orientation and eating attitudes among a subclinical college population and a clinical population of individuals receiving inpatient treatment for eating disorders, particularly among extrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…The relationship between uncontrollable stress and depression was positive for low intrinsic individuals, but negative for high intrinsic individuals (Crystal, Lawrence, & Lisa, 1990). Several studies have demonstrated that intrinsic religious orientation is associated with better physical and mental health (Smith, Richards, & Maglio, 2004;Masters et al, 2005;Salsman & Carlson, 2005). Intrinsic religious orientation is a protective factor against mental illness, while extrinsic religious orientation has been classified as a risk factor in regards with mental illness (Hunter & Merrill, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between uncontrollable stress and depression was positive for low intrinsic individuals, but negative for high intrinsic individuals (Crystal, Lawrence, & Lisa, 1990). Several studies have demonstrated that intrinsic religious orientation is associated with better physical and mental health (Smith, Richards, & Maglio, 2004;Masters et al, 2005;Salsman & Carlson, 2005). Intrinsic religious orientation is a protective factor against mental illness, while extrinsic religious orientation has been classified as a risk factor in regards with mental illness (Hunter & Merrill, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A curvilinear relationship was found between religious orientation and eating attitudes among a subclinical and clinical college population receiving inpatient treatment for eating disorders [4]. On the other hand, Ellison [5] found that the positive influence of religious certainty on wellbeing is direct and substantial.…”
Section: Introductionmentioning
confidence: 99%
“…M. H. Smith, Richards, and Maglio (2004) studied undergraduates and patients at an inpatient treatment program for eating disorders. They discovered a curvilinear relationship among religious orientation and eating disorder symptoms.…”
mentioning
confidence: 99%